PEMBELAJARAN MATEMATIKA REALISTIK DI SEKOLAH DASAR PADA MATERI FPB DAN KPK DENGAN MODEL PENYAJIAN PAKET MAKANAN - Fachrurazi, Fachrurazi (Al-Khawarizmi, 2017)
So far, the concept of the Greatest Common Divisor (GCD) and the Least Common Multiple (LCM) of two numbers are still being taught procedurally whether it is seeking multiples or by understanding prime numbers and prime factorization. This way often makes the students difficulties in determining the GCD and LCM. To overcome such things, the authors will offer a solution in learning mathematics material GCD and LCM in elementary school taught with Approach Realistic Mathematics Education (RME) food package presentation model. Mathematical learning with this approach is believed to make students learn as if they find themselves GCD and LCM concepts learned and will make learning more meaningful so that ultimately will improve students' understanding on GCD and LCM concepts.